(untitled) (Comprehensive Journal of Science, 2025)
One of the fundamental principles of administrative law is the principle of proportionality. This principle indicates that administrative decisions must be appropriate to the objectives of disciplinary decisions. It ensures that the imposed penalties are proportionate to the violation. Appropriateness and proportionality are two sides of the same coin; they both constitute a means of monitoring administrative actions within the system. The state and its administrative bodies, and from this threquirement of applying the principle of proportionality is nothing but the administrative judge examining the subject of the decision; that is, the punishment with the reason for the decision justifying it. If the judge finds a degree of disproportion, he cancels the decision because it is illegal due to violating the law, leaving the administration free to assess the appropriateness of the penalty within the framework of this proportionality, as long as it does not exceed its limits by excess and negligence.